2003
DOI: 10.1155/2003/475603
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Successful Clinical and Laboratory Outcomes in Patients with Primary Sclerosing Cholangitis Undergoing Endoscopic Retrograde Cholangiopancreatography

Abstract: First, in PSC, clinical and laboratory improvement is more common in patients undergoing therapeutic ERCP than diagnostic ERCP. Second, aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase improve following both diagnostic and therapeutic ERCP, and should therefore not be relied upon to determine the success of the procedure. Third, bilirubin levels decreased in the therapeutic group but remained unchanged in the diagnostic group, suggesting that the serum bilirubin level may be a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Several studies have evaluated the risk of complications in PSC patients undergoing ERCP (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). ERCP carries an increased risk for complications in the context of PSC, especially pancreatitis, cholangitis and extravasation of contrast, although not all the studies were documented such an increased risk in PSC (69,74).…”
Section: Esge/easl Suggest That Ercp In Psc Patients Should Be Undertmentioning
confidence: 99%
“…Several studies have evaluated the risk of complications in PSC patients undergoing ERCP (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). ERCP carries an increased risk for complications in the context of PSC, especially pancreatitis, cholangitis and extravasation of contrast, although not all the studies were documented such an increased risk in PSC (69,74).…”
Section: Esge/easl Suggest That Ercp In Psc Patients Should Be Undertmentioning
confidence: 99%
“…PSC is characterized by inflammation and fibrosis of the intrahepatic and extrahepatic bile ducts. The disease is highly variable in its progression, but can eventually lead to cirrhosis and other adverse events including portal hypertension, cholestasis and jaundice, recurrent ascending cholangitis, and cholangiocarcinoma [1][2][3]. The incidence of PSC is approximately 100 per million/year in the United States, with a 10-year survival after diagnosis of approximately 65% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that ERCP may be dangerous for patients with PSC 9,10. In patients with PSC, liver function may be impaired after ERCP.…”
Section: Discussionmentioning
confidence: 99%